Transcending texts and contexts: methodology to investigate media controversies - Chappi Docurro, Tania (2023)
Based on the review and interpretation of theoretical-methodological assumptions related to social communication, journalism, controversy, content analysis in MCM and ideological discourse, this article bases a methodology to investigate media controversies in printed publications, the which is applicable to controversies that circulate in digital media, adapting to the peculiarities of these the variable corresponding to the presentation of the materials involved in the dispute. This proposal allows registering the context of the controversy submitted to scrutiny, its relevance, themes; the characteristics, ideologies and proceeding of the actors; the structuring of the discursive space that the medium grants (location, genres, paratexts); the depth of the debate, its language, tone and resources; its typology; the functions it fulfills; the scope and repercussion within the Communication and Social System. Likewise, it makes it possible to verify the reception that the controversy in question has had in the public sphere.